Quintais agroflorestais em duas localidades na zona rural de Abaetetuba: relato de experiência das vivências dos estágios supervisionados do curso superior de tecnologia em agroecologia - COSTA, William da Silva (2023)
The present text aims to report learning about agroforestry backyards obtained from the experience of the Supervised Internships of the Technology in Agroecology course, Federal University of Pará, University Campus of Abaetetuba. The internship experiences took place from July 18 to 22 and November 21 to 25, 2022, in two family farms, located in the Quilombola Community Ramal do Bacuri and in the Agro-extractive Community Ramal Cataiandeua, both located in the rural area of Abaetetuba, Pará. Among the many exchanges of experiences and knowledge construction with the families that welcomed us into their homes, we highlight the agroforestry backyards, because through them it was possible to experience Agroecology in its essence. The agroforestry backyards are managed based on agroecological practices, which exalt cultures and knowledge passed on from generation to generation, so that families conserve in a very special way the local agrobiodiversity, and contribute through these agroecosystems to a better food and nutritional security for their families.